Avaliação da percepção de pacientes adultos acerca dos efeitos do tratamento orto-cirúrgico na qualidade de vida relacionada à saúde bucal: um estudo misto - Folchini, Stella (2021)
Individuals with facial deformities, as in cases of moderate to severe Class II and III skeletal malocclusions, may experience facial pain and headaches, difficulties with chewing, breathing, sleeping, emotional, social, esthetic and even interpersonal and professional problems. Thus, undergoing orthodontic treatment combined with orthognathic surgery can change the quality of life of these people. This study aimed to evaluate and understand the influence of orthosurgical treatment on oral health-related quality of life (HRQOL) in patients with Class II and III skeletal malocclusions. A mixed study was conducted with a sample consisting of 22 patients, with a mean age of 41 years, from a private practice in the city of Santa Maria, of whom 19 effectively participated. The study took place in the period between March 2020 and July 2021. In its first phase, a cross-sectional study was conducted, in which patients answered the OHIP-14 questionnaire (Oral Health Impact Profile) after conclusion of treatment. The second, qualitative phase was carried out with the same patients immediately after applying the quantitative questionnaire. Questionnaires and interviews were conducted by a single interviewer through the Google meet platform. Quantitative data were analyzed by means of descriptive analysis, and qualitative results by the thematic analysis proposed by Braun & Clark (2006). The overall mean OHIP after treatment was 4.21 SD (4,68). Altogether, 4 themes emerged: concept of quality of life, pre-treatment life, post-treatment life and positive and negative aspects of treatment. It could be observed that having the ortho-surgical treatment performed, positively influenced the esthetic, functional and psycho-emotional aspects of the oral healthrelated quality of life of the patients in the sample.